2016
DOI: 10.1016/j.bbrc.2016.01.071
|View full text |Cite
|
Sign up to set email alerts
|

Senescence from glioma stem cell differentiation promotes tumor growth

Abstract: Glioblastoma (GBM) is a lethal brain tumor composed of heterogeneous cellular populations including glioma stem cells (GSCs) and differentiated non-stem glioma cells (NSGCs). While GSCs are involved in tumor initiation and propagation, NSGCs’ role remains elusive. Here, we demonstrate that NSGCs undergo senescence and secrete pro-angiogenic proteins, boosting the GSC-derived tumor formation in vivo. We used a GSC model that maintains stemness in neurospheres, but loses the stemness and differentiates into NSGC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…For these experiments we chose cell lines GSC 157 and GSC 83, which exhibit PN and MES characteristics, respectively, and could be cultured under conditions known to favour either stemness or differentiation [9]. As previously characterized [16,37], the non-adherent PN GSCs formed tight multicellular spheres with extensive cell-cell contacts (Figure 2(a-b)), expressed high levels of the stem cell marker, prominin 1 (CD133), and almost no CD44 (Figure S3 A-B). They were also virtually negative for glial fibrillary acidic protein (GFAP), which is normally expressed by more mature astrocytes (Figure S3C-D).…”
Section: Resultsmentioning
confidence: 99%
“…For these experiments we chose cell lines GSC 157 and GSC 83, which exhibit PN and MES characteristics, respectively, and could be cultured under conditions known to favour either stemness or differentiation [9]. As previously characterized [16,37], the non-adherent PN GSCs formed tight multicellular spheres with extensive cell-cell contacts (Figure 2(a-b)), expressed high levels of the stem cell marker, prominin 1 (CD133), and almost no CD44 (Figure S3 A-B). They were also virtually negative for glial fibrillary acidic protein (GFAP), which is normally expressed by more mature astrocytes (Figure S3C-D).…”
Section: Resultsmentioning
confidence: 99%
“…GBM146 and 157 GSCs were maintained in serum-free sphere medium, and NSGCs were obtained from these GSCs as previously described [19,20]. Cell proliferation was evaluated using a CellTiter-Glo Luminescent Cell Viability Assay (Promega, Fitchburg, WI, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Cell proliferation was evaluated using a CellTiter-Glo Luminescent Cell Viability Assay (Promega, Fitchburg, WI, USA). Flow cytometry was performed as described [20]. …”
Section: Methodsmentioning
confidence: 99%
“…Aforementioned studies supporting the cancer stem cell hypothesis suggest that multiple cellular populations exist within a tumor, including a self-renewing cancer stem cell population and a less-proliferative differentiated population. A recent paper demonstrated that cells derived from glioma stem cells may differentiate and subsequently undergo senescence [198]. We speculate that phase V tumor cells represent cancer stem cells that may give rise to more differentiated, phase IV cells (Figure 5A).…”
Section: A Model For the Temporal Molecular Pathogenesis Of Gliomasmentioning
confidence: 85%